2011
DOI: 10.1159/000334334
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Dietary Recommendations and Risk of Esophageal Squamous Cell Carcinoma: A Case-Control Study in Iran

Abstract: Background/Aim: The Dietary Guidelines for Americans Adherence Index (DGAI) 2005 was developed to assess the contribution of dietary patterns to chronic disease risk. The objective of this study was to evaluate the association of dietary patterns as measured by the DGAI 2005 with the esophageal squamous cell carcinoma (ESCC) risk in Iran. Methods: This case-control study was conducted on 50 ESCC cases and 100 hospital controls aged 40–75 years. Participants were interviewed using validated food frequency quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 90 publications
1
16
1
Order By: Relevance
“…Both high frequency and long-term intakes were associated with elevated risk of ESCC. This observation is consistent with other studies [16,24,25]. However, the underlying mechanism was still unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Both high frequency and long-term intakes were associated with elevated risk of ESCC. This observation is consistent with other studies [16,24,25]. However, the underlying mechanism was still unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 53 studies retrieved for full-text review, 24 met the selection criteria ( Figure 1 and Table 1 ). UGI cancers were identified by self-reported questionnaire [ 7 , 8 , 10 ], physician-reviewed pathology records [ 7 , 8 , 10 ], linkage to cancer registry system [ 5 , 6 , 7 , 8 , 10 , 11 ], or pathological confirmation [ 9 , 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. All included cohort studies were rated as high-quality (7–9 points) ( Supplementary Material 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Findings from investigations quantifying diet quality based on Chinese Healthy Food Patterns [ 38 ], Dietary Guidelines for Americans Adherence Index [ 24 ], Diet Quality Index [ 12 ], Food Diet Score [ 39 ]; Index of Nutritional Quality [ 40 ] and empirically defined food indices [ 32 ] have demonstrated the beneficiary role of high diet quality in the prevention of UGI cancers. Pooling the findings from two studies assessing diet quality based on HEI [ 6 , 12 ] revealed the preventive effect of high diet quality on UGI cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The complicate interaction of dietary components has promoted the adoption of comprehensive methods to derive dietary patterns. Some priori techniques related to dietary index were adopted to describe dietary patterns (Bosetti et al , 2003; Jessri et al , 2011), but these techniques based on the previous knowledge may not reflect the current status (Reedy et al , 2010). The dietary patterns derived from the posteriori method, such as cluster analysis, factor analysis, and principal component analysis, aggregate variables into the factors representing broad eating patterns of specific population (Reedy et al , 2010).…”
mentioning
confidence: 99%